STUDY ON DYNAMICS MODELING AND RESPONSE CHARACTERISTIC OF BOLTED STRUCTURE WITH THE CONTACT SURFACE CHARACTERISTIC - ZHAI Zhangxin; SUN Yunyun; WU Shijing (Jixie qiangdu)
Considering the actual excitation load, the nonlinear dynamics characteristics of the bolted structure have a certain impact on the whole mechanical system. The dynamics model of actual bolted structure is more complex with considering joint surface morphology parameters and plasticity index. Therefore, with considering the influence of the surface mopography parameters, plastic index on the normal contact stiffness, contact damping and under the various conditions such as external harmonic excitation, the existing normal contact model of bolted structure was modified, and the obtained nonlinear normal contact stiffness and nonlinear contact damping were applied to the dynamics response characteristics analysis of forced vibration of bolted joints structure. The influences of surface morphology parameters and plasticity index on the dynamics characteristics of bolted structure were studied.